Planning Metropolitan Futures, the Future of Metropolitan Planning: In What Sense Planning Agile? - Tewdwr-Jones, Mark; Galland, Daniel (Springer, 2020)
This chapter focuses on the drivers of change affecting metropolitan cities and analyses the current agencies and mechanisms to achieve future planning of places. It constructs a typology of the changing role and context of planning affected by wider political and global forces and sets out the differences between formalised metropolitan planning processes set within institutional settings and government, and more incremental and agile planning processes set within more fluid governance structures. In achieving this, we examine the implications and what is at stake for the future of metropolitan regions and styles of metropolitan governance by identifying the enduring hallmarks of metropolitan planning. The final section puts forward a series of provocations on what a future style of metropolitan planning could be.
Keywords: Metropolregion; Planungsgeschichte; Zukunftsaussicht; Regional Governance; Informelle Planung; Anpassungsfähigkeit; Planungserfordernis; Regionalplanung